The Development of an Electricity Theft Detection System - Muhammad Aaqib; Izhar Ud Din; Musawir Ghani (Pakistan Journal of Engineering & Technology, 2022)
Electricity theft stays a gigantic misfortune brought about by electricity appropriation organizations. This robbery emerges significantly increased when this is done by consumers. For example, meter bypassing, tempering meter, and so on. The main reason for the losses is the direct connection of distribution lines which means Kunda or hooking from electricity lines. So, an intensive method is required to stop this kind of electricity theft. This examination study offers a methodology for taking care of electricity meter bypassing and altering. The overall system is a design based on a GSM module, Arduino Mega, Arduino Nano, and three current sensors, in which one current sensor measures the incoming current from the main grid and the other two sensors measure the current from the consumption side and compare the incoming and consumption current values. When there is any value increase from the compared values, it will detect electricity theft. This method will automatically read and send the current sensor values and also detect electricity theft.